Mengenali Karakter Anak - Wanty Khaira, Muhajir, Aisyah, Firmawati (JKA, 2024)
Child Character Recognition material presented to the head of school at Hotel Linge Aula, Takengon, Indonesia covers the importance of understanding the characteristics of pupils in the learning process, as well as child character formation from an early age. A child's character needs to be shaped from an early age, because at this time it's a critical time to shape a character. Character formation requires a long and not automatic process, the characteristics of the child include ethnic, cultural, social status, interests, cognitive development, initial abilities, learning styles, motivation, emotional development, social development, moral and spiritual development and motoric development. School leaders can play an important role in strengthening school character education through school management, integrating character material into all aspects of the classroom and providing plenty of color for school development. It is hoped that the exposure of this material can bring a change to the world of education especially education of children's character better in the future